Landscape conservation design from the perspective of the obligate species: example for the sagebrush steppe biome - O'Brien, Lee E., author; Hufbauer, Ruth, advisor; Steel, Zachary, advisor; Gavin, Michael, committee member; Morisette, Jeffrey, committee member (Colorado State University. Libraries, 2025)
Conservation strategies in use today are not keeping up with the speed and scale of threats to the natural world. They are not effectively curbing the current wave of species extinctions. There is a critical need to conserve and manage whole landscapes, preserving their ecological integrity, to head off species imperilment. Habitat loss and fragmentation are significant causes of species imperilment, and both habitat amount and contiguity (inverse of fragmentation) must be addressed for effective conservation planning. This study is focused on identifying the location, configuration, and contiguity of environmental and abiotic factors required to sustain the populations of species that are reliant on a particular landscape for some portion of their life histories. I used the sagebrush steppe biome in the western United States to demonstrate how this can be done. Several major issues have heretofore inhibited identifying habitats able to sustain the populations of a wide array of taxa: 1) insufficient data for many species; 2) bias issues with using publicly collected "big data"; 3) inadequate computing capacity for large-extent high-resolution habitat models, and; 4) no explicit way for habitat models to include species-specific habitat connectivity, important for population viability. Some of these issues can be addressed now because of the increasing availability of species location data, increased computational capacities, and better optimization algorithms, and some I propose ways to address. Surmounting these impediments allowed me to identify the fundamental habitats most likely to sustain populations of native species, and use these models as inputs in a systematic conservation planning procedure to identify areas of the sagebrush steppe biome most likely to support the persistence of the obligate taxa using the least amount of land. I compared this approach to using an umbrella species to protect habitats of sympatric species, assessing whether protecting habitats for sage-grouse species, greater sage-grouse (Centrocercus urophasianus) and Gunnison sage-grouse (C. minimus), would protect the other taxa reliant upon the sagebrush steppe landscape. I found that using sage-grouse habitat as an umbrella left many sympatric species with inadequate habitat protection. Determining whether sufficient habitat of sympatric species is protected requires knowing the habitat requirements of these taxa. If the habitat requirements of these taxa are determined, as done in this study, each species' required habitat can be included in a conservation plan, instead of relying on the assumption that conserving an umbrella species' habitat will provide sympatric species protection adequate to secure their persistence. The approach developed here has additional advantages. Namely, as new information becomes available, the fundamental habitat models for species can be updated and included in the conservation plans. Also, the amount of species fundamental habitat required or supplemental goals (e.g., including core sagebrush, threats, or sage-grouse protection areas) can be easily added to the optimization routine to produce new optimal multi-species habitat configurations. This gives conservation planners the means to explore explicit effects and tradeoffs of pursuing different conservation objectives, while assuring the resulting plans can support the persistence of the obligate taxa of a biome.
Keywords: conservation; landscape; sagebrush; design; biome; planning